The Role of Work Motivation to Improve Employee Performance at PT Asuransi Umum Bumiputera Muda 1967 Banjarmasin Branch - Trisylvana Azwari; Novi Shintia; Anita Dwi Rahmadhani (PT. Hanken Sukses Jaya, 2022)
Based on observations seen by researchers at PT Asuransi Umum Bumiputera Muda 1967 in improving employee performance, employees are faced with obstacles that arise, namely in a pandemic like this the monthly target and the number of files on the employee's desk so that employees need time to search for files on their desks. The purpose of this study is to determine the role of work motivation so far that has been carried out at PT Asuransi Umum Bumiputera Muda 1967 Banjarmasin branch to improve employee performance. The method that the authors use in conducting this final project research is using descriptive statistical analysis techniques. Descriptive statistical analysis is a technique used to analyze data by describing or describing the data that has been collected as it is by making calculations based on numbers. Researchers can conclude that the right work motivation to improve employee performance at PT Asuransi Umum Bumiputera Muda 1967 Banjarmasin branch is as follows: Achieving targets, Great tolerance between co-workers, Self-motivation to work optimally, Company leaders always try to discuss the problems that occur on how to give gifts that are evenly distributed to all employees and agents, not only those who reach the target, so that employees and agents are more active in doing the assigned tasks and have high morale